Determining the membrane properties (A, B, S) for deformable membranes utilized in pressure and osmotically driven membrane processes - Sim, Yi Ting (Nanyang Technological University, 2020)
Seawater desalination, despite being an attractive solution to mitigating global freshwater shortage, is neither economically nor environmentally sustainable at this stage due to high energy and cost requirements as well as environmental issues pertaining to brine disposal. RO desalination technology is a popular, lower energy consuming and more economically viable solution than evaporative methods but is limited by the pressure membranes can withstand and hence the concentration of brine it can treat. These limitations prevents seawater desalination from becoming economically viable as the small volumes of water recoverable makes the process highly inefficient and costly due to the size of treatment systems required and cost of chemicals for pre-treatment to treat sufficient volumes of seawater to meet demands. The high volumes of brine generated also creates environmental issues and further costs to be borne to treat the brine to global disposal standards. These limitations can be easily overcome by introducing other forms of membrane desalination technologies like the OARO process. However, OARO is more affected by the concentration polarization phenomena as it involves the use of saline solutions on both sides to offset osmotic pressure which can adversely affect membrane performance. Therefore, the knowledge of the membrane properties, A, B, and S are extremely crucial as they are used to determine membrane performance under certain operating conditions which in turns determines the suitability of membranes for pressure and osmotically driven membrane processes. Current conventional methods used to derive A, B, and S suggests that the membrane properties, being physical intrinsic properties, should remain constant regardless of operating conditions but has been refuted by research as an erroneous assumption. Building upon that, research was performed in this project to attest the validity of the hypothesis and proposed method that a single experiment is sufficient to accurately determine A, B, and S of deformable membranes subjected to a wide range of hydraulic pressures, and postulates that the outcome will allow for more accurate predictions of the membrane properties to model each process more accurately under any feed and draw concentration. Indeed, the methods proposed validates the hypothesis as reflected by the results which are in line with the desired outcomes.